Partnerships for subject specific global information services. Section 10 - Sinha, P.K. (CGIAR System Organization, 1994)
This paper looks into the establishment of a new livestock research cnetre which would play a key role in defining and executing a CGIAR livestock strategy. It discusses partnerships for global information on animal agriculture with particular reference to a model which has been developed to provide information services in support of global research on livestock. The model envisages the creation of a global database of important national, regional and international information centres and networks providing information on livestock. This is to identify partners and seek partnerships. The specific partnerships are outlined. The sucess of the system described in the model is also examined.